BALINESE SPIRITUAL CULTURE-BASED HEALTH COMMUNICATION: THE ROLE OF JERO BALIAN IN CONVEYING THE MEANING OF ILLNESS AND RECOVERY - Pande Mirah Dwi Anggreni (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2025)
Health communication in the Balinese context is not merely about delivering medical information but also encompasses social and spiritual processes in interpreting illness and recovery. This study aims to explain the construction of culture-based spiritual health communication in Bali through the practices of Jero Balian as a mediator between the dimensions of sekala (the physical world) and niskala (the spiritual realm). The study employs a qualitative-descriptive method with an ethnography of communication approach, based on literature review and case observations in Balinese communities. The findings reveal that Jero Balian’s communication practice integrates three main forms: verbal communication through mantras and ritual language; nonverbal communication through gestures, symbols, and sacred acts; and transcendental communication through spiritual dialogue between humans and the niskala forces. These forms function as a symbolic communication system that interprets illness as spiritual disharmony and healing as a reconstruction of cosmic balance. The study implies that Bali’s culture-based health communication is holistic and humanistic, offering an alternative model to modern medical practice that emphasizes harmony of the physical, mental, social, and spiritual dimensions of health.